The Effects of Good Governance and Internal Control Systems on Government Performance: An Empirical Study in Madiun Regency - Wibisono , Nurharibnu; Sari, Syarifah Ratih Kartika; Widayati , Tria (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study aims to: (1) analyze the effect of good governance on the performance of the Madiun Regency Government, (2) analyze the effect of the internal control system on the performance of the Madiun Regency Government, and (3) analyze the joint effect of good governance and the internal control system on the performance of the Madiun Regency Government. The study population included all government offices within Madiun Regency, with a total of 18 offices. The sample was selected using a purposive sampling technique, consisting of 36 leaders from these offices. Data were analyzed using multiple linear regression with the SPSS program. The results indicate that good governance does not have a significant effect on government performance. In contrast, the internal control system was found to have a significant positive effect on performance. Furthermore, good governance and the internal control system jointly have a significant effect on the performance of the Madiun Regency Government